On Visual Texture Preference: Can an Ecological Model Explain Why People Like Some Textures More Than Others?. (May 2016) - Stephens, Kyle D.; Hoffman, Donald D.
What visual textures do people like and why? Here, we test whether the ecological valence theory proposed for color preferences can also predict people's preferences for visual texture. According to the theory, people should like visual textures associated with positive objects or entities and dislike visual textures associated with negative objects or entities. We compare the results for the ecological model with a more traditional texture-preference model based on computational features and find that the ecological model performs reasonably well considering its lower complexity, explaining 63% of the variance in the human preference data.